2017
DOI: 10.1111/ppa.12761
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of adult plant resistance to leaf rust in a wheat association mapping panel

Abstract: Leaf rust caused by Puccina triticina is one of the most destructive fungal diseases of wheat (Triticum aestivum). Adult plant resistance (APR) is an effective strategy to achieve long‐term protection from the disease. In this study, findings are reported from a genome‐wide association study (GWAS) using a panel of 96 wheat cultivars genotyped with 874 Diversity Arrays Technology (DArT) markers and tested for adult leaf rust response in six field trials. A total of 13 quantitative trait loci (QTL) conferring A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Furthermore, we observed that STB resistance in SAMP is not linked to the HD as reported earlier by Arama et al (1999) and Simón et al (2005). The genomic regions associated with STB resistance were located at different genetic positions compared with HD QTL identified in SAMP (unpublished data) and in previously reported QTL for HD (Risser et al, 2011;Zanke et al, 2014;Gerard et al, 2017;Huang et al, 2018;Li et al, 2019;Sheoran et al, 2019). Using HD as a covariate, QTL for heading date were mapped on chromosome 2A (6 and 17 cM), whereas STB QTL was mapped on chromosome 2A; SRT_SAT2_3, SRT_SAT2_4, and APS_SAT17_11 were located far apart on 92, 104, and 97 cM, respectively (Supplementary Figure 4).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, we observed that STB resistance in SAMP is not linked to the HD as reported earlier by Arama et al (1999) and Simón et al (2005). The genomic regions associated with STB resistance were located at different genetic positions compared with HD QTL identified in SAMP (unpublished data) and in previously reported QTL for HD (Risser et al, 2011;Zanke et al, 2014;Gerard et al, 2017;Huang et al, 2018;Li et al, 2019;Sheoran et al, 2019). Using HD as a covariate, QTL for heading date were mapped on chromosome 2A (6 and 17 cM), whereas STB QTL was mapped on chromosome 2A; SRT_SAT2_3, SRT_SAT2_4, and APS_SAT17_11 were located far apart on 92, 104, and 97 cM, respectively (Supplementary Figure 4).…”
Section: Discussionsupporting
confidence: 78%
“…Genome-wide association mapping (GWAM) is an effective statistical approach for evaluating the strength of the association between any phenotypic trait and a marker locus (George and Cavanagh, 2015). It has been widely used to identify QTL for various traits in wheat such as root length (Ayalew et al, 2018), resistance to foliar diseases (Juliana et al, 2015;Gerard et al, 2017;Kidane et al, 2017;Ayana et al, 2018;Li et al, 2019;Yates et al, 2019), grain yield (Ward et al, 2019), coleoptile length (Li et al, 2017), and heat tolerance (Maulana et al, 2018;Tadesse et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the seedling resistance gene Lr28 is located on 4AL [51,62], Lr28 associated SSR markers wmc313, gwm160 and barc78 [63] are about 105 cM distant from the SNP markers defining QLr.spa-4A on our map. The only other resistance reported on 4AL was by Gerard et al [64] but their QTL is located in a similar region as Lr28/Sr17. None of the four other cultivars we studied harbored QLr.spa-4A making Lillian the exception.…”
Section: Qtl Detected In a Single Cultivarmentioning
confidence: 90%
“…Up to now, 5 QTL have been described on chromosome 6BS, but only QLr.caas-6BS.1, derived from the wheat cultivar Bainong 64, was physically localized in the region between 32 and 34 Mbp (Gerard et al 2018;Kankwatsa et al 2017;Ren et al 2012). Gerard et al (2018) stated that another QTL (QLr.wpt-6BS.2) is genetically located in the same region as QLr.caas 6BS.1, whereas QLr.wpt-6BS.2 was mapped close to the centromere, a region clearly distinct from QLr.jki-6B.1 (Table 5). Therefore, further studies are required to confirm whether our QTL is located closely to these known QTL.…”
Section: Discussionmentioning
confidence: 99%
“… QLr.cim-5AC wPt-3187–wPt-7769 Na–464.7 Avocet-YrA × Kenya Kongoni (RIL) Calvo-Salazar et al ( 2015 ) QLr.jki-6B.1 AX-94739546–TA003005.0339 19.3–34.3 BMW population Novel? QLr.caas-6BS.1 Xcfd13–Xwmc487 34.2–36.5 Bainong64 × Jingshuang16 (DH) Ren et al ( 2012 ) QLr.wpt-6BS.2 wPt2175 na b Winter wheat accessions Gerard et al ( 2018 ) QLr.jki-6B.2 wsnp_Ex_c54772_57528275–Excalibur_c29748_954 710.1–719.7 BMW population Lr3 ? QLr.cim-6BL 277,143–1,234,305 714.3–na Bairds × Atred#1 (RIL) Lan et al ( 2017 ) 6B_4 BobWhite_c43263_180–BS00011795_51 718.9–720.6 Elite spring wheat lines Gao et al ( 2016 ) QLr.jki-7A.1 BobWhite_rep_c58252_112–wsnp_BF473884A_Ta_1_3 54.9–71.1 BMW population Novel QLr.jki-7A.2 RAC875_c75528_355–BS00024786_51 79.6–na BMW population Novel?…”
Section: Discussionmentioning
confidence: 99%